Juridical Analysis of the Culpa in Causa Principle in Indonesian Criminal Law Reform (Study of Law No. 1 of 2023) - Dyajeng Ayu Musdalifah; Ali Masyhar (Universitas Islam Sultan Agung, 2025)
The explicit integration of the culpa in causa principle in Pasal 55 of Law No. 1 of 2023 one the New Indonesian Criminal Code (KUHP Baru) refolutionizes criminal law by limiting the misuse of grounds for exemption from punishment, such as necessity and self-defense, when the offender intentionally creates those conditions. Unlike the old KUHP’s implicit reliance on jurisprudence, this provision strengthens the geen straf zonder schuld principle while balancing judicial pardon authority, through proof of subjective causality via at least two valid pieces of evidence. Courts distinguish it from objective justifications by analyzing initial intent, nullifying subsidiarity without eliminating the defendant’s subjective fault. Impacts include optimized restorative justice, legal certainty, reduced impunity from provocation, and proportional individualized sanctions, fostering an adaptive penal system that protects victims while upholding humanity. This reform aligns continental doctrines with national contexts, enhancing judicial legitimacy.